2015
DOI: 10.1111/jftr.12069
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Father Families: A Review of the Literature

Abstract: The number of children residing in single‐father families in the United States quadrupled as a proportion of children's living arrangements during the past few decades of the 20th century. Research on single fathers also increased and changed in nature. This article is a review of the research on single fathers and their families from the 1970s until recently, focusing on modifications in methodology and theoretical underpinnings. In general, research on single‐father families evolved from qualitative studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 60 publications
5
55
1
5
Order By: Relevance
“…Conversely, higher levels of maternal rejection are associated with greater behaviour problems such as aggression [73,74]. Moreover, there is evidence that single fathers have weaker interpersonal and affective bonds with their children, and exhibit less supervision and monitoring [75], compounding the possible effects of mother absence. However, the current results prohibit us from drawing firm conclusions, and these interpretations thus remain speculative, and future research is needed to understand the exact underlying processes of family influence on adolescents' experiences of violence victimisation and perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, higher levels of maternal rejection are associated with greater behaviour problems such as aggression [73,74]. Moreover, there is evidence that single fathers have weaker interpersonal and affective bonds with their children, and exhibit less supervision and monitoring [75], compounding the possible effects of mother absence. However, the current results prohibit us from drawing firm conclusions, and these interpretations thus remain speculative, and future research is needed to understand the exact underlying processes of family influence on adolescents' experiences of violence victimisation and perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these moderators distinguishes the perceptions of relationship quality from youth with male or female caregivers. Overwhelmingly, the literature examining parental gender effects on children's behaviour has found that children who are parented by males are at increased risk for a broad range of negative social and emotional outcomes (Coles, 2015). It was anticipated that youth with male primary caregivers would report lower quality relationships than would youth who were cared for by women.…”
Section: Caregiver Gendermentioning
confidence: 99%
“…More is known about the role of male caregivers in the development of juvenile delinquency generally. Coles (2015) demonstrated that youth living with only male caregivers were more likely to engage in delinquent behaviour or be diagnosed with an externalising disorder than those living in households with women. Similarly, Breivik and Olweus (2006) found that youth living solely with single-fathers had significantly higher levels of externalising problems than did children living with single mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Census Bureau, 2016). Although many single-parent households thrive, in general they face challenges such as reduced financial resources, limited social support, social stigma, and constraints on time spent with their children (Coles, 2015;McLanahan & Sandefur, 1994). While all types of single-parent families challenge the normative preference for two-parent families, the single gay fathers in California and Texas's gay fathers' groups can best be characterized as single parents by choice.…”
Section: In Visible Families 36mentioning
confidence: 99%